Energy Prices and Their Direct Effect on Inflation in Serbia during 2016-2025 - Miljković, Marko; Molnar, Dejan; Tanasković, Svetozar (Industrija, 2026)
Over the past fifteen years, inflation in Serbia has generally remained low and within the NBS target range, except during the period from 2021 to 2023. The aim of this paper is to assess the direct contribution of energy prices to inflation in Serbia. Energy accounts for approximately 16% of the consumer basket, and fluctuations in energy prices influence non-core inflation, which includes price growth that is prone to significant short-term oscillations due to supply shocks. The paper examines the price trends of electricity, gas, solid fuels, heat energy, and fuel for passenger vehicles, as well as the effects of changes in these prices on overall inflation in Serbia from 2016 to 2025. Throughout most of this period, the direct contribution of energy prices to inflation was less than one percentage point a year, representing between 15% and 30% of the total contribution of all components of the consumer basket. The largest impact on inflation was due to rising electricity prices, followed by increases in fuel prices for passenger vehicles and solid fuels.